The learning issues in engineering statics - Haron, Habibah; Mohd. Shaharoun, Awaluddin; Harun, Hafizah (Common Ground Publisher, 2009)
Rate of failure in a fundamental course in an undergraduate engineering program has been found to affect the time to graduate for many Mechanical Engineering students at a government-funded university in Malaysia. Data from the academic session 2004/2005 to 2007/2008 showed an average of 34 percent of students per semester not graduating on time. Compared to other pre-requisite and follow-on courses, students’ achievements in ‘Statics’ which students took as their first engineering course in the first year showed an average of 21 percent failures per semester for semesters 1-2004/2005 to 2-2007/2008, with the highest record of 46 percent and the lowest of 13 percent. Among these students 19 percent managed to pass after retaking the course for the third time and another 15 percent were either terminated or withdrew from the program. Based on this initial analysis, a study was conducted to examine the pedagogical issues related to the teaching and learning (T&L) of Statics. The main concerns were highlighted and will be the basis for identifying appropriate strategies for improvement. Implications from the findings would be useful to those involved in academia